Pre-Islamic Arab Political Marriages and Tribal Alliances - Jasim, Hassan Mohammed; Al-Kanzawi, Muhannad Abdul-Ridha Hamdan (Indonesian Journal of Islamic Studies, 2026)
General Background: Marriage in pre-Islamic Arab society functioned as a central social institution linking tribes and consolidating authority. Specific Background: Historical narratives document numerous unions between kings, tribal leaders, and prominent families aimed at securing loyalty and stabilizing political relations. Knowledge Gap: Despite scattered references in classical sources, systematic discussion of political marriage alliances as structured mechanisms of tribal governance remains limited. Aim: This study examines forms, objectives, and consequences of political intermarriages among Arab tribes before Islam. Results: The findings show that such marriages created durable kinship bonds, facilitated negotiation, reduced intertribal hostilities, strengthened leadership legitimacy, and occasionally failed, leading to renewed conflict. They functioned as strategic instruments for alliance-building, territorial security, and consolidation of power. Novelty: The study synthesizes dispersed historical accounts into a coherent analytical framework that positions marriage as a deliberate political strategy rather than merely a social custom. Implications: Understanding these alliances clarifies patterns of authority formation and conflict resolution in pre-Islamic Arabia and provides deeper insight into the socio-political foundations inherited by early Islamic society.Highlights: Marriage functioned as a political alliance mechanism. Kinship bonds structured tribal governance and authority. Alliances sometimes prevented conflict but could also fail. Keywords: Pre-Islamic Arabia; Political Marriage; Tribal Alliances; Arab Kings; Kinship Networks